SCHIZOTYPY – CURRENT CONCEPTS AND FUTURE RESEARCH IMPLICATIONS - Ristić, Ivan; Marić, Nađa P.; Maksimović, Nataša; Knežević, Goran (Medicinski podmladak, 2019)
Schizotypy is a construct used to describe a group of persons with symptoms which do not fulfill criteria for schizophrenia, but have some similarities with this complex and heterogeneous psychiatric disorder.  ICD-10 describes schizotypy as a state (schizotypal disorder), while DSM-5 labels it as a trait marker (schizotypal personality disorder). Considering how schizotypy encompasses through the normal, subclinical and clinical population, a thorough theoretical understanding of this concept could be helpful in developing measures of assessment. So far, most of the tools for psychometric evaluation of schizotypy have focused only on abnormal personality.  The present article focuses on the evolution of the term schizotypy, its current understanding, the possibilities of psychometric assessment in relation to contemporary constructs of personality and on clinical considerations for improved detection and intervention in this field.